ANALISIS RESPON SISWA SMK PGRI SUKOHARJO TERHADAP PEMBELAJARAN MATEMATIKA MELALUI MEDIA ONLINE - Tri Puji Astuti; Joesefin Indriayudea; Titich Estu Hastuti; Annisa Prima Exacta (Absis: Mathematics Education Journal, 2020)
The objective of this study is to find out the results of the analysis of student responses to mathematics learning through online media. This is descriptive quanlitative study that focuses on learning evaluation using online media. The population are students of class X TBSM, XI OTKP, and XI AKL SMK PGRI Sukoharjo. The sample are selected using simple random sampling technique. The data collection instrument using an online learning questionnaire and for the data analysis use descriptive statistics. The results show that student learn using online media as very effective (7.90%), most of them rated it as effective (34.2%) and ordinary (28.9%). There are also students who considered online learning as ineffective (21.1%) and very ineffective (7.90%). To make mathematics learning even more effective, teachers or educators are further expected to apply the seven principles given by students, namely (1) Learning through video calls, (2) Providing brief learning materials, (3) Providing videos in delivering material, (4) Minimize sending material in the form of large files to save mobile data, (5) Material selection in the video must be based on language criteria that is easy to understand, (6) Keep providing material before assignments, (7) Reducing assignments